El aislamiento social como escenario propicio para autorregular el aprendizaje (Memorias Sifored - Encuentros Educación UAN, 2021)
Self-regulation of learning became a fundamental axis for academic achievement in the midst of the social isolation caused by Covid-19. This scenario, in which the internet became for many institutions as the only means to end the academic period, provided tools, changed the role of the teacher in the teaching and learning processes and promoted in students, situations in which they had to become aware of your learning. To determine which self-regulation learning strategies used by a group from the first semester of Social Communication-Journalism from a higher education institution and their respective progress in the following academic period, a mixed methodology of a mixed explanatory sequential approach (DEXPLIS) was implemented, under which it was found that critical thinking and the regulation of metacognition as key aspects to encourage self-regulation strategies of learning within the classroom.